An unusual colonoscopic complication of inflammatory bowel disease - Türkel Küçükmetin, Nurten; Çiçek, Bahattin; Baba, Füsun (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Türkel Küçükmetin N, Çiçek B, Baba F. An unusual colonoscopic complication of inflammatory bowel disease. Turk J Gastroenterol 2020; 31(3): 272-3.